8-MW wind turbine tower computational shell buckling benchmark. Part 2: Detailed reference solution. (June 2023) - Sadowski, Adam J.; Seidel, Marc
Highlights: Fully reproducible worked solution to computational WTST benchmark. Illustration of automatable, geometrically scalable meshing protocol. Illustration of prEN 1993-1-6-compliant GMNIA imperfection amplitude calibration. Eigenmode and weld depression imperfections require different calibrations. Benchmark makes start of public repository of GMNIA verification examples. Abstract: An assessment of the elastic–plastic buckling limit state for multi-strake wind turbine support towers poses a particular challenge for the modern finite element analyst, who must competently navigate numerous modelling choices related to the tug-of-war between meshing and computational cost, the use of solvers that are robust to highly nonlinear behaviour, the potential for multiple near-simultaneously critical failure locations, the complex issue of imperfection sensitivity and finally the interpretation of the data into a safe and economic design. This paper presents a detailed reference solution to the computational buckling analysis of a standardised benchmark problem of an 8-MW multi-strake wind turbine support tower. Both linear and nonlinear analyses are performed, including advanced GMNIA with several different models of geometric imperfections. The crucial issue of interpreting the imperfection amplitude in a way that is compliant with the new prEN 1993-1-6 is discussed in detail. The solution presented herein is intended for use by analysts in both industry and academia for training, verification and calibration of finite element models and is intended to initiate a public repository of such computational solutions for metal civil engineering shell structures. This paper is the second of a pair. The first paper [37] presents a synthesis of 29 submissions to an international round-robin exercise performed on the same benchmark problem.